2020
DOI: 10.3390/su12218899
|View full text |Cite
|
Sign up to set email alerts
|

An Early Flame Detection System Based on Image Block Threshold Selection Using Knowledge of Local and Global Feature Analysis

Abstract: Fire is one of the mutable hazards that damage properties and destroy forests. Many researchers are involved in early warning systems, which considerably minimize the consequences of fire damage. However, many existing image-based fire detection systems can perform well in a particular field. A general framework is proposed in this paper which works on realistic conditions. This approach filters out image blocks based on thresholds of different temporal and spatial features, starting with dividing the image in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In Hsu et al [12] (2020), a flame color analysis method is proposed based on modified rules presented in [11]. The authors observed that [11] performs well for low-intensity fires, where dominant colors are red and yellow.…”
Section: E Hsv Hsl and Hwb Color Spacesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Hsu et al [12] (2020), a flame color analysis method is proposed based on modified rules presented in [11]. The authors observed that [11] performs well for low-intensity fires, where dominant colors are red and yellow.…”
Section: E Hsv Hsl and Hwb Color Spacesmentioning
confidence: 99%
“…When the background noise is successfully removed, the method for extraction of flame pixel might require less restrictive rules. Some examples of color spaces that are used in the literature are RGB [10], YCbCr [11] [12], and CIELab [13]. Other methods combine different color spaces to increase the chance of detection of flame pixels, such as the methods that combine HSV, HSL, and HWB [14], and RGB and YCbCr [15] color spaces.…”
Section: Introductionmentioning
confidence: 99%
“…The research method has less computational time. Still the algorithm shows more false alarm rate which is caused by the shaking of camera (Hsu et al 2020).The optical remoting sensing system is used in the fire warning system to alert the people who are living nearby the forest. This system depends on the camera resolution and view of the angel.…”
Section: Research Articlementioning
confidence: 99%
“…Although vision-based sensing systems have shown good performance, massive and complex datasets often delay the time in the decision-making process [ 17 ]. Thus, visual-based sensing systems are not appropriate for early fire detection where decision making needs to be conducted in limited time.…”
Section: Introductionmentioning
confidence: 99%